2014
DOI: 10.4236/crcm.2014.34045
|View full text |Cite
|
Sign up to set email alerts
|

Primary Leiomyosarcoma of the Ovary: A Case Report

Abstract: Leiomyosarcoma of the ovary is a rare disease, with aggressive behavior and poor prognosis, which mainly occurs in postmenopausal women. Surgery is the cornerstone of treatment, while the role of chemotherapy and radiotherapy is still not clear because substantial data is lacking. This paper presents the case of an adult woman who is diagnosed with primary leiomyosarcoma of the left ovary, and who receives a surgical approach and adjuvant treatment with chemotherapy currently achieving 20 months free from dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…However, postsurgical radiotherapy may aid in achieving local control and chemotherapy has been recommended for stages II to IV, where in most cases ifosfamide-based regimens have been used; cisplatin-based regimens have also been described. 22 In our case, the tumor was completely excised and the patient received adjuvant chemotherapy with adriamycin. However, the patient developed disseminated metastatic disease and is currently alive with disease 17 months after surgery.…”
Section: Discussionmentioning
confidence: 81%
“…However, postsurgical radiotherapy may aid in achieving local control and chemotherapy has been recommended for stages II to IV, where in most cases ifosfamide-based regimens have been used; cisplatin-based regimens have also been described. 22 In our case, the tumor was completely excised and the patient received adjuvant chemotherapy with adriamycin. However, the patient developed disseminated metastatic disease and is currently alive with disease 17 months after surgery.…”
Section: Discussionmentioning
confidence: 81%
“…In a 58-year-old postmenopausal woman with Stage Ia leiomyosarcoma of ovary, Zygouris et al reported no evidence of recurrence 21 months after initial surgery, without any postoperative adjuvant therapy [6]. In another report of primary leiomyosarcoma of the ovary, adjuvant treatment with ifosfamide and doxorubicin was used, achieving progression-free survival of 24 months and overall survival of 36 months [7].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of vague and non-specific symptoms leiomyosarcoma is diagnosed at an advanced stage and often with distant metastases mainly to lungs and liver [21,22]. Recurrences within the first year after diagnosis are common, mainly in the pelvis and abdomen [30].…”
Section: Characteristicsmentioning
confidence: 99%
“…The histogenesis of this neoplasm remains ambiguous as ovary does not contain smooth muscles and there are many possible locations from which the neoplasm may develop [26]. These include: totipotent ovarian mesenchyme, smooth muscle fibers of ovarian ligaments, the vascular wall, Wolfian duct remnants, smooth muscle metaplasia of ovarian stromal or theca cells or smooth muscle cells that migrate from within the uterus [25,26,29,30]. Leiomyosarcoma can also develop within teratoma, papillary serous cystadenocarcinoma or serous cystadenoma [26].…”
Section: Characteristicsmentioning
confidence: 99%